CE: Assessing a Child's Pain. Issue 5 (May 2019) - Freund, Debra; Bolick, Beth N.
Abstract : N/A: Effective pain assessment is a necessary component of successful pain management and the pursuit of optimal health outcomes for patients of all ages. In the case of children, accurate pain assessment is particularly important, because children exposed to prolonged or repeated acute pain, including procedural pain, are at elevated risk for such adverse outcomes as subsequent medical traumatic stress, more intense response to subsequent pain, and development of chronic pain. As with adults, a child's self-report of pain is considered the most accurate and reliable measure of pain. But the assessment of pain in children is challenging, because presentation is influenced by developmental factors, and children's responses to certain features of pain assessment tools are unlike those commonly observed in adults. The authors describe the three types of assessment used to measure pain intensity in children and the tools developed to address the unique needs of children that employ each. Such tools take into account the child's age as well as special circumstances or conditions, such as ventilation requirements, cognitive impairment, and developmental delay. The authors also discuss the importance of proxy pain reporting by the parent or caregiver and how nurses can improve communication between the child, caregiver, and health care providers, thereby promoting favorable patient outcomes. Abstract : This article discusses the factors that can influence a child's report of pain, describes components of a comprehensive pediatric pain assessment, and reviews appropriate pain assessment scales for children of different ages and levels of cognitive development.